Preliminary study on the identification of synthetic cathinones in street seized samples by Raman spectroscopy and chemometrics. (1st February 2021) - Braz, André; Santos Silva, Carolina; Peixoto, Ana Christina; Pimentel, Maria Fernanda; Pereira, Goreti; Caixeta Castro Souza Braga, Patrícia; Martini, André Luiz; Lino Fernandes Alcântara, Thaynara
Abstract: Synthetic cathinones are new psychoactive substances that are a menace to public health worldwide and a real forensic challenge. Given the recent changes in the Brazilian legislation that bans the generic structure of these substances, the forensic workflow of drug analysis has the opportunity to speed up the arrests by in loco screening analysis. This preliminary study investigated the use of portable Raman spectrometer and chemometrics for fast, direct, and non‐destructive presumptive identification of three synthetic cathinones in seized packages and confirmatory analysis using FTIR. The 40 samples were analyzed directly and included three 3, 4‐methylenodioxy substituted cathinones and other legal and illegal substances that were identified by two police forces in Brazil. Due to lack of reference Raman spectra, a purification step of the cathinone samples was performed. PCA showed that the spectral region 1, 560–1750 cm −1 was the most important region for differentiating these types of cathinones from the other substances. MCR‐ALS was used to resolve the spectral mixture of signals from adulterants and identify the presence of cathinones in the seizures. The purified spectra were used as initial estimates. The concentration profiles for each component indicated significant contributions of two characteristic bands around 1, 606 and 1, 680 cm −1 . Additionally, analysis of the optimized spectral profiles showed Raman shifts and differences in the relative intensity of those bands which allowed discrimination among the samples. Band attribution of infrared spectra confirmed the results obtained with screening method. The method proposed has potential for objective and contactless identification of seized synthetic cathinones. Abstract : Screening method using portable Raman spectroscopy and Multivariate Curve Resolution–Alternating Least Squares for objective and contactless identification of seized synthetic cathinones.